Conservation et disparition des repères de crue – Exemple des repères apposés après la crue de 1930 en Lot-et-Garonne et dans le sud du Tarn - François Gazelle; Klaus Maronna (Physio-Géo)
In order to show the levels reached by major flood events at significant points, and in order to record the information for future reference, the law promoted by BACHELOT in July 2003 places an obligation on municipal councils and state-run bodies to put in place visible markers, a practice which is not new but which had tended to die out while it was not a statutory requirement. It is reasonable to raise the question of the conservation of these markers over the decades. With this in mind, the authors made use of archival data and carried out field investigations in order to determine the presence or absence of markers put in place after the flood of 1930 in two areas of south-western France, and to establish the causes of the disappearances that they found.